2017
DOI: 10.1002/rhc3.12128
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Down Uncertain Risks for Risk Communication: A Conceptual Review of the Environmental Health Literature

Abstract: In this conceptual review, we describe how the concept of "uncertain risk" is addressed in thePALABRAS CLAVES: comunicació n de riesgos, gestió n de riesgos, incertidumbre

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…In our context this means that there is not necessary a one-to-one relationship between a type of crisis and a type of response, but that the same types of collaborative response can be effective for different types of crisis and vice versa. The crisis typology developed by The International Risk Governance Council (IRGC, 2008; an updated version published by Florin & Bürkler (2017), on the contrary, is more concerned with keeping types of risk issues presented (simple, uncertain, complex, and/or ambiguous) separate from the description of possible designs for risk management strategies ("risk-informed," "robustness-focused", "precaution-based," "resilience-focused," and "discourse-based" strategies) (Jansen, Claassen, van Poll, van Kamp, & Timmermans, 2018). This typology has, however, two other disadvantages in the light of our line of argument.…”
Section: Development Of a Typology Of Infectious Disease Threatsmentioning
confidence: 99%
“…In our context this means that there is not necessary a one-to-one relationship between a type of crisis and a type of response, but that the same types of collaborative response can be effective for different types of crisis and vice versa. The crisis typology developed by The International Risk Governance Council (IRGC, 2008; an updated version published by Florin & Bürkler (2017), on the contrary, is more concerned with keeping types of risk issues presented (simple, uncertain, complex, and/or ambiguous) separate from the description of possible designs for risk management strategies ("risk-informed," "robustness-focused", "precaution-based," "resilience-focused," and "discourse-based" strategies) (Jansen, Claassen, van Poll, van Kamp, & Timmermans, 2018). This typology has, however, two other disadvantages in the light of our line of argument.…”
Section: Development Of a Typology Of Infectious Disease Threatsmentioning
confidence: 99%
“…Within the studied sample, the aspects used to describe their understanding of the concept of 'uncertain risk' varied within and between groups. Some individuals described multiple epistemic uncertainties found in Jansen et al (2017), while others (including experts) described only one. Additionally many different associations were found in the participants' descriptions of the concept of 'uncertain risk' (Appendix A).…”
Section: Resultsmentioning
confidence: 99%
“…Tosun (2013) defines uncertain risks as '[ … ] situations in which the relationship between activities and their potential hazard cannot be established'. In order to further clarify the scientific meaning of the concept 'uncertain risk' we conducted a conceptual review of the environmental health literature (Jansen et al 2017) and tried to answer about what aspects of risk uncertainty exists (location of uncertainty) when scientists refer to 'uncertain risk'. The review showed that the uncertainty about the presence or existence of risk may be the result of six different epistemic uncertainties (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, "(un)intended misinterpretation of uncertainty is large", which makes risk communication in case of uncertain risks challenging and often used as a strategy toward influencing public health policies, either to reject or to demand policy action. 4 Indeed, despite this lack of research and scientific consensus around COVID-19, political and institutional speech has reflected a relative certainty about the disease, its evolution and the measures taken. 5 This contrasts with the acknowledgment that "no previous training, no prior strategic planning knowledge, no prior operational experience, and no former decision-making skillset has prepared anyone for the uncertainty surrounding what this complex new reality presents us with."…”
mentioning
confidence: 99%